Tuberculosis in Pregnancy and Its Impact on Children: Tuberculosis - Satrinawati Berkat (Journal of Midwifery and Community Health (JMCH), 2026)
TB during pregnancy not only impacts the mother's health but also the health of the fetus she carries until the baby grows into adulthood. Impacts on the fetus include miscarriage, intrauterine death, stillbirth, low birth weight, premature birth, and congenital TB. Meanwhile, the impact on the baby after birth and toddlerhood includes impaired growth and development, making them susceptible to severe TB symptoms